Gender preferences, socio-demographic and health risks associated with preferred preventive-promotive benefit packages of health insurance for women in Perak and Selangor, Malaysia - Nurul Azwa Mohd Ismail,; Sharifa Ezat Wan Puteh,; Khadijah Shamsuddin,; Supasit Pannarunothai,; Hanin Farhana Kamaruzaman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Given the escalating cost of healthcare, Malaysia has to consider implementing social health insurance to provide better financial health protection to the population, especially women. Women are vulnerable to financial distress because they need more complex healthcare needs than men. Therefore, this study will examine the perception among the Malaysian population towards preferred preventive/promotive benefit packages of health insurance for women by analyzing preferences among men and on women’s health services. This study determined respondents’ preferences towards preventive/promotive benefit packages for women using a cross-sectional study conducted in two states; Perak and Selangor from December 2016 to December 2017. This study looked at gender preferences and socio-demographic variables, health risks, and subscription to health insurance to preventive/promotive benefit packages preferences for women. A total of 638 respondents in the 18- to 60-year-old age group were drawn from both genders in this study. Analyzes used logistic regression to determine predictors of preventive/promotive benefit packages preferences for women. The results from the analysis showed that more women (66.7%) significantly preferred preventive/promotive services compared to 58.7% of males (p<0.05). In the multivariate analysis among women, Malay ethnicity (OR 2.42, 95% CI 1.37-4.24), self-employed (OR 6.24, 95% CI 2.41-16.10) and not-working/pensioner (compared to the civil servant; OR 2.71, 95% CI 1.35-5.40), obese (OR 16.24, 95% CI 4.50-58.62), no chronic illness (OR 3.72, 95% 2.01-6.88), and subscribed to health insurance (OR 4.21, 95% CI 1.33-5.52) were the factors associated with women’s preferences towards preventive/promotive benefit packages. Meanwhile, for men, age less than 40-year-old (OR 3.56, 95% CI 1.82-6.95), higher education (OR 3.40, 95% CI 1.77-6.52), self-employed (OR 4.65, 95% CI 2.01-10.72), ex-smoker (OR 5.17, 95% CI 1.42-18.75), heavy physical activity (OR 1.26, 95% CI 1.13-1.52), pre-obese (OR 5.35, 95% CI 2.03-14.05) and obese (compared to underweight; OR 2.28 95% CI 1.18-4.36), and subscribed to health insurance (OR 2.72, 95% CI 1.33-5.52), were associated with men’s preferences towards preventive/promotive benefit packages. The overall results of this study show the importance of socio-demographic factors, health risks, and subscription of health insurance among men and women towards the preferences for women’s benefits packages of health insurance.